2019
DOI: 10.1177/1947603519865318
|View full text |Cite
|
Sign up to set email alerts
|

No Effect of Platelet-Rich Plasma Injections as an Adjuvant to Autologous Cartilage Chips Implantation for the Treatment of Chondral Defects

Abstract: Background Repair of chondral injuries using cartilage chips has recently demonstrated clinical feasibility. Autologous platelet-rich plasma (PRP) is a potential promising technique for improving healing response during cartilage repair. Purpose To assess the cartilage repair tissue quality after autologous cartilage chips treatment (CC) with and without repeated local injections of PRP for the treatment of full-thickness focal chondral defects of the knee. Materials and Methods Two full-thickness chondral def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
0
11
1
Order By: Relevance
“…The Göttingen minipig chondral defect model has previously been described by our group. 29,45-47 Briefly, after premedication with Zoletil mix 1 mL/10 kg (tiletamin 2.5 mg/mL, zolazepam 2.5 mg/mL, torbugesic 0.5 mg/mL, ketaminol 2.5 mg/mL, and rompun 2.5 mg/mL; Virbac, Denmark), general anesthesia and local analgesia were achieved with Etomidate (Hypnomidate, 0.25 mL/kg; Janssen Pharmaceuticals), sevoflurane (3%; AbbVie, Denmark), fentanyl (0.175 mL/kg/h; Hameln Pharmaceuticals), and lidocaine (Xylocaine 10 mL, 20 mg/mL; Astra Zeneca, Denmark). Preoperatively, prophylactic antibiotics were administered (penicillin procaine, 0.03 mL/kg; Ceva Sante Animale, France).…”
Section: Methodsmentioning
confidence: 99%
“…The Göttingen minipig chondral defect model has previously been described by our group. 29,45-47 Briefly, after premedication with Zoletil mix 1 mL/10 kg (tiletamin 2.5 mg/mL, zolazepam 2.5 mg/mL, torbugesic 0.5 mg/mL, ketaminol 2.5 mg/mL, and rompun 2.5 mg/mL; Virbac, Denmark), general anesthesia and local analgesia were achieved with Etomidate (Hypnomidate, 0.25 mL/kg; Janssen Pharmaceuticals), sevoflurane (3%; AbbVie, Denmark), fentanyl (0.175 mL/kg/h; Hameln Pharmaceuticals), and lidocaine (Xylocaine 10 mL, 20 mg/mL; Astra Zeneca, Denmark). Preoperatively, prophylactic antibiotics were administered (penicillin procaine, 0.03 mL/kg; Ceva Sante Animale, France).…”
Section: Methodsmentioning
confidence: 99%
“…However, there is contradictory evidence in PRP effect and cartilage repair, which is not the focus of this review. 48-50…”
Section: Scientific Aspects Of Implantationmentioning
confidence: 99%
“…After 6 months repair, tissue showed features of mature hyaline cartilage both macroand microscopically. In 2019, Olesen et al 33 compared the use of autologous fragmented cartilage in chondral defects of mini pigs with and without the addition of platelet rich plasma. The authors found approximately 20% hyaline cartilage, 50% fibrocartilage, and 22% fibrous tissue in both groups, and concluded that the addition of platelet rich plasma had no beneficial effect on repair.…”
Section: Animal Studiesmentioning
confidence: 99%